Projeto integrado para coleta de dados em redes de sensores sem fio - Felipe Domingos da Cunha (2009)
In Wireless Sensor Networks, the nodes have severe energy constraints due to the fact of having a small battery and being located in places of difficult access for humans. Therefore, these networks need protocols that are efficient regarding energy consumption. Unlike the traditional networks that are designed to accommodate a wide variety of applications, WSNs are usually designed considering very specific applications. Taking into account the great peculiarity of these applications, you can achieve significant improvements in performance if the control and sharing of information among two or more layers are optimized so that the interactions between them are better exploited. This technique is named cross-layer design and has received much attention from researchers in the area of WSNs in recent years. The cross-layer approach enables a strong interaction between two or more layers in the protocols stack and allows the sharing of information at runtime. The objective of this work is to analyze the performance of a cross-layer design to facilitate the adjustment of the duty cycle depending on the network traffic. Thus, it is proposed the algorithm for the link layer SMAC-DDC (Sensor-MAC with Dynamic Duty Cycle) that receives the information from the network layer to adjust the length of the duty cycle of sensor nodes with the objective of reducing the energy consumption and improve data collection. Results of simulations show that it is possible to reduce the latency and energy consumption of a network without compromising the rate of delivery of data to the sink node.